Political Connection, Foreign Ownership, and Tax Avoidance: Does Executive Gender Moderate the Relationship? - Limpat Akbar Yudanto; Theresia Woro Damayanti (Universitas Hayam Wuruk Perbanas, 2021)
Tax revenue is a vital source of income to support the economic development of acountry. Therefore, this study aims to provide empirical evidence of the influence ofpolitical connections and foreign ownership on tax avoidance. This study also analyzes the moderating role of executive gender on the influence of politicalconnections and foreign ownership on tax avoidance. This study used secondary panelÂ data from a survey conducted by the World Bank Open from 2006-2018. This study'sÂ data was around 50,454 companies from all over the world. The hypothesis testingÂ was performed using multinomial logistic regression. The results showed thatpolitical connection positively affected tax avoidance, but foreign ownership had nosignificant effect on tax avoidance. Furthermore, male executives strengthened therelationship between political connections and tax avoidance, but it did not moderatethe effect of foreign ownership on tax avoidance. The findings suggested that theDirectorate General of Taxation should scrutinize companies with political connections to optimize government tax revenue.